التعددية اللغوية في الجزائر - سيدي محمد, بلقاسم (Université de M'sila, 2017)
لا شك أن اللغة وسيلة للتعبير عما يدور في خلجات النفس من أفكار، بغية إخراجها إلى عالم الحس و الإدراك الخارجي, فهي خير أداة للتفاهم والتواصل بين أفراد المجتمع ، ناهيك عن كونها كائنا حيا ينمو و يتطور ، ليحقق ارتقاء لغويا يساير الارتقاء العقلي و الحضاري. و لقد كانت اللغة العربية و لا تزال ذاكرة الأمة التي تختزن تراثها و قيمها ، و الهوية التي تميزها عن غيرها و تمدها بمجموعة الخصائص التي تحمل في ثناياها معاني القومية و الوحدة و الاستمرارية. و لا يخفى على أحد أن هذه اللغة تعاني من بعض الأمراض التي تحاصرها من كل حدب و صوب , لتجعل منها عرضة للكثير من الأخطار في محاولة لهدم عرشها و تقويض أركانها. و يظهر ذلك جليا من خلال ظاهرة التعدد اللغوي بشقيه الثنائية اللغوية والازدواجية اللغوية. و من ثمة فإن الهدف الأساسي من هذه الدراسة ، هو استيعاب حقيقة هذا الوضع المتسم بالتعددية اللغوية ومحاولة الوصول إلى أبعاده على مستوى بلادنا وإدراك انعكاساته من خلال الإجابة على السؤال المحوري الذي يمثل إشكالية البحث و الفلك الذي يدور فيه : ما مدى تأثير كل من الازدواجية اللغوية و الثنائية اللغوية على اللغة العربية الفصحى؟ وما هو وضع اللغة العربية في الجزائر؟ ما مدى تفاعلها مع غيرها؟ Abstract Language is the divine gift of the god , it is an extremely important way of interacting with the people around us .Without language we cannot communicate with people. As it is a vital tool for communication .This living and growing organism contribute to the linguistic development to keep pace with mental and cultural progression . It should be noted also, that language can’t remain as it is , so it create a lot of variants of dialects and different languages Arising therefrom . Moreover the contact with other languages is one of the most important reasons to help his growth , and As a result it has appeared multiple patterns in the use of one language by the single individual and within a single society. It is common knowledge that Arabic language was and is still the memory of the nation which used to store its heritage, values, and identity that set them apart and provide a set of properties that carries the meanings of nationalism , unity and continuity. But no one doubts that this language suffer from some diseases that are trapped on all sides , and make it vulnerable to many dangers in the attempt to demolish her throne, and to undermine its pillars. And it appears evident through the phenomenon of multilingualism to both bilingualism and duplication of language. It may seem at first glance that linguistic diversity is a cultural enrichment, however this multilingualism may occur a serious struggle, especially when there are difficulties in the acquisition of the native language which is the case in some Arab countries, and Algeria in particular . And from there, the main goal of this study is defining the concept of multilingualism and adjust its terminology, and then examine its manifestations and the reasons for its occurrence in order to study the language situation in Algeria.
Keywords: multiple؛ unity؛ phenomeno؛ manifestations؛ the language situation